LBA54ENTRATA: Randomized, double-blind, phase II study of telaglenastat (tela; CB-839) + everolimus (E) vs placebo (pbo) + E in patients (pts) with advanced/metastatic renal cell carcinoma (mRCC). (1st October 2019) - Motzer, R J; Lee, C-H; Emamekhoo, H; Matrana, M; Percent, I; Hsieh, J J; Hussain, A; Vaishampayan, U N; Graham, R; Liu, S; McCune, S; Shaheen, M; et al.
Abstract: Background: Altered glucose and glutamine (gln) metabolism is a hallmark of RCC. Glutaminase (GLS) is a key enzyme in gln metabolism and drives proliferation of RCC cells when overexpressed. Tela, a novel, first-in-clinic, selective GLS inhibitor, blocks critical gln-dependent pathways and synergizes preclinically with signal transduction inhibitors (eg, E). In a phase I study in mRCC, telaE was well tolerated and had encouraging clinical activity. We present here results of a randomized phase II study of telaE vs pboE in 3L+ mRCC (NCT03163667). Methods: Eligible pts had ≥2 prior lines of systemic therapy for mRCC, including ≥1 VEGFR-targeted tyrosine kinase inhibitor (TKI), KPS ≥70%, and measurable disease (RECIST 1.1). Pts were stratified by prior lines of TKI and MSKCC risk and randomized 2:1 to receive tela (800 mg PO BID) or pbo, plus E (10 mg PO QD), until disease progression/unacceptable toxicity. Primary endpoint is investigator-assessed progression-free survival (PFS) (RECIST 1.1; 1-sided alpha <0.2). Results: 69 pts were randomized (Table). Median PFS was 3.8 mo for telaE vs 1.9 mo for pboE (HR = 0.64 [95% CI, 0.34-1.20], 1-sided P = 0.079).Gr ≥3 adverse events (AEs) occurred in 80% telaE pts vs 60% pboE; most common were anemia (17% vs 17%), pneumonia (7% vs 4%), abdominal pain (7% vs 0%), thrombocytopenia (7% vs 0%), fatigue (4% vs 9%). Discontinuation rates due to AEs were similar (28% telaE, 30% pboE). There were no treatment-related deaths. Subgroup analyses were consistent w/ primary analysis. Survival data will be presented. Conclusions: The addition of tela improved PFS over pboE, w/ tolerable safety profile in heavily treated mRCC pts, including refractory to multiple TKIs and immune checkpoint inhibitors. ENTRATA met its primary endpoint, supporting proof of concept for GLS inhibition w/ tela as a new therapeutic approach in RCC. Clinical trial identification: NCT03163667; May 23, 2017. Editorial acknowledgement: Medical writing support was provided by Ingrid Koo, PhD, and funded by Calithera Biosciences, Inc. Legal entity responsible for the study: Calithera Biosciences, Inc. Funding: Calithera Biosciences, Inc. Disclosure: R.J. Motzer: Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Advisory / Consultancy: Novartis; Advisory / Consultancy, Research grant / Funding (institution): Genentech/Roche; Advisory / Consultancy: Exelixis; Advisory / Consultancy: Merck; Advisory / Consultancy, Research grant / Funding (institution): Eisai; Advisory / Consultancy: Incyte; Advisory / Consultancy: Lilly; Research grant / Funding (institution): Bristol-Myers Squibb. C. Lee: Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution): Eisai; Advisory / Consultancy, Research grant / Funding (institution): Exelexis; Advisory / Consultancy: Amgen; Advisory / Consultancy, Research grant / Funding (institution): BMS; Research grant / Funding (institution): Calithera; Research grant / Funding (institution): Pfizer; Leadership role: Kidney Cancer Association. H. Emamekhoo: Advisory / Consultancy: Exelixis; Advisory / Consultancy: Bayer. M. Matrana: Speaker Bureau / Expert testimony: Merck; Speaker Bureau / Expert testimony: Genentech; Speaker Bureau / Expert testimony: BMS; Speaker Bureau / Expert testimony: Eisai; Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Speaker Bureau / Expert testimony: Janssen; Advisory / Consultancy: Strata Oncology. J.J. Hsieh: Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution), Research funding for Kidney Cancer Therapeutics; Institutional funding for clinical trials: Eisai; Advisory / Consultancy, Research grant / Funding (self), Research funding for Kidney Cancer Genomics: Novartis; Research grant / Funding (self), Research funding for Kidney Cancer Genomics: BostonGene; Research grant / Funding (self), Research funding for Kidney Cancer Genomics: Cancer Genetics Inc; Research grant / Funding (institution), Institutional funding for clinical trials: Calithera; Research grant / Funding (institution), Institutional funding for clinical trials: BMS; Research grant / Funding (institution), Institutional funding for clinical trials: Exelixis; Leadership role, Medical Steering Committee: Kidney Cancer Association. A. Hussain: Advisory / Consultancy, Consultant; Site PI for sponsored clinical trial: Bayer; Advisory / Consultancy, Advisory Board: AstraZeneca; Advisory / Consultancy, Consultant: Bristol-Myers Squibb; Advisory / Consultancy, Advisory Board: Exelexis; Research grant / Funding (institution), Site PI for sponsored clinical trial: Sotio; Research grant / Funding (institution), Site PI for sponsored clinical trial: Calithera; Research grant / Funding (institution), Site PI for sponsored clinical trial: Merck; Research grant / Funding (institution), Site PI for sponsored clinical trial: Roche; Research grant / Funding (institution), Site PI for sponsored clinical trial: Constellation; Research grant / Funding (institution), Site PI for sponsored clinical trial: Clovis. U.N. Vaishampayan: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Research support: BMS; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Research support: Exelixis; Advisory / Consultancy, Speaker Bureau / Expert testimony: Bayer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Sanofi; Research grant / Funding (self), Research support: Novartis; Leadership role, Board Member: Michigan Society of Hematology Oncology. S. Liu: Honoraria (self): Merck; Honoraria (self): Exelixis. S. McCune: Research grant / Funding (institution), PI on this trial for our institution: Calithera. H. Parmar: Shareholder / Stockholder / Stock options, Full / Part-time employment: Calithera Biosciences. Y. Shen: Shareholder / Stockholder / Stock options, Full / Part-time employment: Calithera Biosciences. S.H. Whiting: Shareholder / Stockholder / Stock options, Full / Part-time employment: Calithera Biosciences; Spouse / Financial dependant: Seattle Genetics. N.M. Tannir: Research grant / Funding (self), Research grant / Funding (institution), Principal Investigator on clinical trials; institutional - direct costs on clinical trials: Calithera. All other authors have declared no conflicts of interest.